1963
DOI: 10.1002/pol.1963.100010702
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance of polypropylene

Abstract: SynopsisRadicals produced in Co60 irradiated normal and l,l&-polypropylene have been examined by electron spin resonance. It is concluded that 80% of the radicals are -CH2--CH(CH, )-and 20'33 are -CH2-C(CH1)-CH2in both atactic and isotactic polymer. In the isotactic, but not in the atactic material, the primary radical disappears much faster than the secondary one when heated. Interpretation of the spectra of polybutylene and polyisobutylene is also given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1970
1970
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 1 publication
2
8
0
Order By: Relevance
“…Copolymers. In the reported studies of radicals formed in polypropylene by ionizing115,179,679, 708,838,851,855,1031,1149,1265,1326,1363,1392,1481,1483,1487,1569,1570,1640,1652,1664,1665,1812,1994,2307,2467,2488) and neutron837 ) radiation, many radical structures have been proposed.Irradiation of polypropylene at 77 K gives formation of radicals (5.12) which are observed as eight-or nine-line ESR spectra(Fig. Formation Under Ionizing Radiation.…”
mentioning
confidence: 99%
“…Copolymers. In the reported studies of radicals formed in polypropylene by ionizing115,179,679, 708,838,851,855,1031,1149,1265,1326,1363,1392,1481,1483,1487,1569,1570,1640,1652,1664,1665,1812,1994,2307,2467,2488) and neutron837 ) radiation, many radical structures have been proposed.Irradiation of polypropylene at 77 K gives formation of radicals (5.12) which are observed as eight-or nine-line ESR spectra(Fig. Formation Under Ionizing Radiation.…”
mentioning
confidence: 99%
“…[17][18][19] The spectrum shape of FeCl3-ab- sorbing PP sample closely resembled to that of FeC13-free PP sample, but a somewhat lower signal intensity was observed. Dependence of the relative signal intensity on the FeC13 concentration is shown in Figure 2.…”
Section: Irradiation With High-pressure Mercury Lamp Under Nitrogenmentioning
confidence: 53%
“…Kauzmann and Eyring (2) were the first workers to infer from the rheological changes in polymers during shearing that mechanical scission of carbon-carbon bonds was occurring in the polymer backbone. This has subsequently been confirmed by ESR ( 3 ,4) and studies by Watson and his coworkers (5,7 ) showed that in the absence of oxygen the macro-radicals produced by mechanical scission of the polymer molecule (Scheme 1 , reaction (a)) were effective initiators for radical polymerization.…”
Section: Degradation Reactions In Polymersmentioning
confidence: 78%